Penyuluhan Pola Hidup Sehat Pada Lansia - Iis; Ela Rohaeni; Elsa Almanda; Nabila Nurfarah F.; Anisa Dwi Nurmala; Nena Khairunnisa (Health Care : Journal of Community Service, 2025)
The elderly are an age group that is susceptible to various degenerative diseases and decreased physical function, so they require special attention in maintaining their health. A healthy lifestyle is an important factor in improving the quality of life of the elderly. However, the results of the Self-Awareness Survey conducted in RW 04 Mayung Village showed that most elderly people still have low knowledge regarding healthy lifestyles. This community service activity aims to increase the elderly's understanding of the importance of a healthy lifestyle through counseling and elderly exercise activities. The method used is direct health education through interactive lectures and joint exercise activities, which were held on Saturday, July 6, 2024 at the RW 04 Mayung Village Health Center with 25 elderly participants. The results of the activity showed an increase in knowledge and enthusiasm of the elderly in implementing a healthy lifestyle, such as maintaining a diet, exercising regularly, and checking their health regularly. This activity is expected to contribute to forming positive habits in the elderly and become a sustainable program that involves the active role of the community and local health workers.